Characteristics of Renal Cell Carcinoma in Dr. Hasan Sadikin General Hospital Bandung, 2010–2014 - Dicky Suryana Putra; Sri Suryanti; Aaron Tigor Sihombing (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Data characteristics for renal cell carcinoma are mostly derived from developed countries. However, data from developing countries, specifically in Indonesia have not been fully described. This study aimed at describing renal cell carcinoma (RCC) characteristics based on age, gender, and histopathology type in Dr. Hasan Sadikin General Hospital Bandung.Methods: This was a descriptive study conducted in August–October 2015. The data were collected from histopathology medical records of patients who had been diagnosed with RCC at Department of Pathology Anatomy Dr. Hasan Sadikin General Hospital Bandung, from 2010 to 2014. Total sampling was used as sampling method. Only RCC records that had complete variables; which were age, gender, and histopathological type; included in this study.Results: There were 25 cases of renal cell carcinoma discovered in this study, 17 cases discovered in men and 8 cases discovered in women. The histopathology type found in this study was clear cell renal cell carcinoma (12 cases), papillary renal cell carcinoma (8 cases), chromophobe renal cell carcinoma (3 cases), and carcinoma of the collecting ducts of bellini (2 cases). There were no cases found below the age range 2–29 years old and above the age range 70–79 years old.Conclusions: Men have higher incidence than women with the ratio of 2:1. Peak incidence is found on the age range 50–59 years old. The most common histopathology type is clear cell renal cel carcinoma.[AMJ.2016;3(4):644–8] DOI: 10.15850/amj.v3n4.953